Outcome of Locking Compression Plate (LCP) Fixation of Diaphyseal Radius-Ulna fracture in Patients of 50 Years and Above - Khan, Md Tanvir Ahasan Juglol; Mia, Mohammad Mohsin; Mehnaz, Kh Sabiha; Md Ekram; Alam, Muhammad Monjurul; Jhilky, Most Tasnim Ara (Mugda Medical College Journal, 2025)
A prospective, observational study was conducted at National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh, from January 2018 to December 2019, to evaluate the effectiveness of locking compression plate (LCP) fixation in treating diaphyseal forearm fractures. A total of 34 adults aged 50 and above, a population with a high prevalence of osteoporosis, were selected for this study. With an average follow-up period of 25.27±1.39 weeks, the study found that older age and delayed surgery correlated with poorer outcomes, while motor vehicle accidents accounted for 52.94% of the injuries. The average time to radiological union was 12.18±1.53 weeks, with one case of nonunion and a complication rate of 11.76%. At the final follow-up, the mean range of motion for flexion-extension and supination-pronation was 133.53°±5.44° and 124.41°±11.19°, respectively, and the mean Quick DASH score was 14.6%±7.14%. According to the Anderson criteria, 50% of cases were rated as excellent, 47.06% as good, and 2.94% as poor. The study concludes that LCP fixation is an effective treatment for diaphyseal forearm fractures in this age group, demonstrating favorable outcomes regarding union rates, pain management, and functional recovery, with meticulous surgical technique being key to optimal results. Mugda Med Coll J. 2024; 7(2): 95-101